2017
DOI: 10.15309/17psd180117
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Treatment of Lupus: Effects of Three Intervention Conditions

Abstract: ______________________________________________________________________RESUMO: Lúpus eritematoso sistêmico (LES) é uma doença autoimune e multissistêmica. Ocorre predominantemente no gênero feminino. O tratamento é diversificado e contém regras complexas, dificultando a adesão. Esta pesquisa estudou os efeitos de três condições de intervenção sobre comportamentos de adesão ao tratamento em mulheres com LES. Trata-se de um estudo longitudinal com coleta de dados em intervalos de 30, 60, 90 e 120 dias. Participar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…According to Gimenes (2010, 2012) and Selvan et al (2017), recordings in self-monitoring forms favor installation of selfobservation behavior, which are requirements for contingency arrangements related to adherence to treatment, as observed by Neder et al, (2017). In this study P1, P2 and P4's reports indicated good acceptance to do the recordings in SMRFs, despite imprecisions; while P3, with the lowest TAI among the participants during the research, reported that she had had diffi culty, and even refused to fi ll out the SMRF, which could explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Gimenes (2010, 2012) and Selvan et al (2017), recordings in self-monitoring forms favor installation of selfobservation behavior, which are requirements for contingency arrangements related to adherence to treatment, as observed by Neder et al, (2017). In this study P1, P2 and P4's reports indicated good acceptance to do the recordings in SMRFs, despite imprecisions; while P3, with the lowest TAI among the participants during the research, reported that she had had diffi culty, and even refused to fi ll out the SMRF, which could explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…JSLE treatment involves the association of a set of guidelines: medication administration, skin protection, well-balanced diet, physical exercises, vaccination, periodic medical examinations and frequent laboratory tests (Dunbar-Jacob, Houze, Kramer, Luyster, & McCall, 2010;Gualano et al, 2011;Klack, Bonfá, & Borba, 2012;Neder, Ferreira, & Carneiro, 2017;Silva et al, 2010). To evaluate treatment effi cacy the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) is used: a quantitative system of evaluation of lupus activity during the last 10 days, with score ranging between 0 (no characteristic of the disease is manifested) and 105 (severe manifestation of all characteristics) (Mikdashi & Nived, 2015).…”
Section: Effects Of Instruction and Self-monitoring On Adherence To Tmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE can affect various systems of the human body, such as the immune, circulatory, nervous, cardiopulmonary, hematological and renal systems [2][3] . Its clinical spectrum varies from mild to severe, with periods of exacerbation and remission 4 .…”
Section: Introductionmentioning
confidence: 99%